2017
DOI: 10.3390/v9090263
|View full text |Cite
|
Sign up to set email alerts
|

Viruses of Microbes

Abstract: Viruses of microbes encompass all viruses that infect archaea, bacteria, and single-celled eukaryotes, especially algae and protozoa [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The human body is colonized by a variety of microbes, including bacteria, fungi, virus, archaea, and protozoa (Grice and Segre, 2012, Sender et al, 2012, Debarbieux et al, 2017, Eckburg et al, 2003, most of which are found in the gastrointestinal tract (Shreiner et al, 2015). Healthy lungs were long considered to be sterile.…”
Section: The Gut-lung Axis and Microbial Dysbiosismentioning
confidence: 99%
“…The human body is colonized by a variety of microbes, including bacteria, fungi, virus, archaea, and protozoa (Grice and Segre, 2012, Sender et al, 2012, Debarbieux et al, 2017, Eckburg et al, 2003, most of which are found in the gastrointestinal tract (Shreiner et al, 2015). Healthy lungs were long considered to be sterile.…”
Section: The Gut-lung Axis and Microbial Dysbiosismentioning
confidence: 99%
“…vi) Astroviridae : In recent years, bats have been found to harbor a great diversity of astroviruses, which raises the inevitable question of its zoonotic potential [ 20 ]. Astroviruses have been considered to be strictly species-specific.…”
mentioning
confidence: 99%